Nauczyciel akademicki – pomiędzy autonomią, zaangażowaniem i nihilizmem - Kwieciński , Zbigniew (Studia Edukacyjne, 2018)
Contemporary culture offers and constantly enriches many models of life, values, and consumption incentives. Pedagogy is also pluralistic today, rich in currents and trends. Teachers, including academics, face the unavoidable and constant choice between getting involved in the work with students and detachment and autonomy, or rather encouraging young people to choose their own identity and orientation, because all choices are equal. It is necessary to seek a common minimum of formal and material goals of upbringing. One of such formal purposes is that of independent judgment, i.e. the autonomy and the ability to think critically. Human is inseparable from the material; there is a dispute, however, about the components of this category. Recognition of the equality of all cultural discourses leads to nihilism with all its consequences.